2016
DOI: 10.1007/s10508-016-0828-x
|View full text |Cite|
|
Sign up to set email alerts
|

A Qualitative Investigation of the Impact of a Livelihood Intervention on Gendered Power and Sexual Risk Behaviors Among HIV-Positive Adults in Rural Kenya

Abstract: Despite the recognized links between food insecurity, poverty, and the risk of HIV/AIDS, few randomized trials have evaluated the impact of livelihood interventions on HIV risk behaviors. The current study draws upon data collected from a qualitative process evaluation that was embedded into a pilot randomized controlled trial that tested whether a multisectoral agricultural intervention (Shamba Maisha) affected the HIV-related health of HIV-positive adults in rural Kenya. In the current study, we drew upon lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…We integrated a longitudinal qualitative study into the pilot trial, aiming to unpack the mechanisms behind intervention impacts (Zakaras et al, 2016). The purpose of the current manuscript is to explore the mental health impacts of the intervention.…”
Section: Data Collectionmentioning
confidence: 99%
“…We integrated a longitudinal qualitative study into the pilot trial, aiming to unpack the mechanisms behind intervention impacts (Zakaras et al, 2016). The purpose of the current manuscript is to explore the mental health impacts of the intervention.…”
Section: Data Collectionmentioning
confidence: 99%
“…In an ongoing longitudinal qualitative study, this intervention also improved ART adherence and clinic attendance, and reduced HIV-related stigma and discrimination [157]; its impacts on stigma were hypothesized to occur through restoration of health, increased social integration, and an increased ability to make reciprocal economic contributions to community safety nets [158]. The same study also found changed gendered power dynamics, reduced high-risk behaviors, and improved prioritization of health [157,159].…”
Section: Promising Approaches To Economic and Livelihood Interventionsmentioning
confidence: 89%
“…Both microcredit studies with FSW found that combined interventions comprised of HIV risk reduction support and multiple HES components including microcredit, were associated with self-reported risk reduction, and one found a reduction in STI incidence though the study quality was low (Odek et al, 2009;Souverein et al, 2013). Finally, adult PLHIV in Kenya participating in a qualitative study cited in the previous section of this paper, reported reduced behaviors associated with onward transmission of HIV resulting from a combined intervention, including microcredit (Zakaras et al, 2016).…”
Section: Promotion Interventionsmentioning
confidence: 74%
“…A qualitative study with an adult female population in Kenya reported that participation in an IGA was not protective against HIV risks, including IPV (Gnauck et al, 2013). A final qualitative study with an HIV-positive adult population in Kenya found an IGA plus an in-kind loan for farming inputs reduced behaviors associated with onward transmission of HIV (Zakaras et al, 2016).…”
Section: Protection Interventionsmentioning
confidence: 99%